Fraser Syndrome: Reporting Two Cases and Reviewing the Literature - Çelik, Hüsnü; Akin, Haluk; Sapmaz, Ekrem; Parmaksiz, Cem; Altingül, Aygen; Akpolat, Nusret; Yekeler, Hayrettin (My University, 2003)
OBJECTIVE: To present two cases with Fraser syndrome diagnosed prenatally and to review the related literature. CASES: First case diagnosed at the 19th gestational week with suggestive ultrasonographic findings and a history of a previous child with Fraser Syndrome. Second pregnancy was terminated at the 36th week of pregnancy because of abnormal ultrasonographic findings such as oligo/anhydramnios, dilated bladder and absent kidneys. This infant died soon after birth due to laryngeal atresia. Post mortem examinations and autopsy findings were suggestive of Fraser Syndrome. CONCLUSION(s): Fraser Syndrome is a rare disease inherited in an autosomal recessive manner. Prenatal ultrasonographic findings and a history of similarly affected fetus may guide to prenatal diagnosis.
Fraser Sendromu: İki Olgu Sunumu ve Literatürün Gözden Geçirilmesi
Keywords: Fraser Syndrome; Prenatal Diagnosis